Bringing up to date the toolkit for the catabolism of aromatic compounds in fungi - Martins, Tiago M. (2024)
Funding Information: The authors are grateful to Maria C. Leitão (ITQB-NOVA Small Molecules Analysis) for the implementation and support in the chromatographic analyses. Mass spectrometry data were generated by the Mass Spectrometry Unit (UniMS), ITQB/iBET, Oeiras, Portugal. All members of the Silva Pereira lab are also thanked for useful discussions. Publisher Copyright: © 2023 The Authors. Microbial Biotechnology published by Applied Microbiology International and John Wiley & Sons Ltd.